(untitled) (The Agriculturists, 2012)
The present study was conducted to estimate the impacts of price and price variability on acreage allocation of rice and wheat production in Bangladesh. Time series data of price and acreage allocation of rice and wheat production during 1983-84 to 2007-08, collected from Bangladesh Bureau of Statistics (BBS) were used in this study. Compound growth rate and Nerlovian models were used. The study indicated that the wholesale price of rice and wheat had significant impact on the allocation of land for rice and wheat production. Significant price variability was found both in case of rice and wheat crop in short-run (SR) and long-run (LR). The values of Nerlovian coefficients of adjustment were found low, which means that although the farmers were adjusting to the changing levels of price, price variability, yield, etc the adjustment was not rapid. Therefore, it may be concluded that the price of rice and wheat should be adjusted rapidly along with allocation of rice and wheat production in Bangladesh. DOI: http://dx.doi.org/10.3329/agric.v10i1.11061 The Agriculturists 2012; 10(1): 23-30